Characterization of the sex-specific pattern of angiogenesis and lymphangiogenesis in aortic stenosis - Matilla, Lara; Martín-Núñez, Ernesto; Garaikoetxea, Mattie; Navarro, Adela; Vico, Julieta Anabela; Arrieta, Vanessa; García-Peña, Amaia; Fernández-Celis, Amaya; Gainza, Alicia; Álvarez, Virginia; Sádaba, Rafael; López-Andrés, Natalia; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective We aim to analyze sex-related differences in angiogenesis and lymphangiogenesis in aortic valves (AVs) and valve interstitial cells (VICs) from aortic stenosis (AS) patients. Approach and Results Totally 230 patients (59% men) with severe AS undergoing surgical valve replacement were recruited. The density of total neovessels was higher in AVs from men as compared to women. Both small and medium neovessels were more abundant in men's AVs. Accordingly, male AVs exhibited higher CD31 and VE-cadherin expressions. The levels of the pro-angiogenic markers, such as vascular endothelial growth factor (VEGF)-A, VEGF receptor (VEGFR)1, VEGFR2, insulin-like growth factor-binding protein-2 (IGFBP-2), interleukin (IL)-8, chemerin, and fibroblast growth factor (FGF)-7, were increased in AVs from men. Transforming growth factor-β expression was higher in male AVs. The expression of antiangiogenic molecules thrombospondin (Tsp)-1, endostatin, and CD36 was upregulated in male AVs, although the levels of Tsp-2, IL-4, IL-12p70, and chondromodulin-1 were similar between both sexes. The number of lymphatic vessels and the expression of the lymphangiogenic markers Lyve-1 and D2-40 was higher in men's AV as well as VEGF-C, VEGF-D, and VEGFR3. Multivariate analyses adjusted for confounders further validated the sex-dependent expression of these targets. VICs isolated from men's AVs secreted higher amounts of the pro-angiogenic factors, VEGF-A, VEGFR1, IGFBP-2, and FGF-7, as well as the pro-lymphangiogenic factors, VEGF-C, VEGF-D, and VEGFR3, than women without changes in antiangiogenic markers. Conclusion Our data show that aberrant angiogenic and lymphangiogenic cues are over-represented in male AVs. Importantly, the VIC is a relevant source of multiple morphogens involved in angiogenesis and lymphangiogenesis likely endowing the AV of men with the predominant calcific AS phenotypes.